Analysis of Related Factors With the Activity of the Larva Monitoring Officer in Disease Control Efforts Dengue Hemorrhagic Fever In Tangerang District - Wahidin, Wahidin; Mansyur, Muchtaruddin; Herman, Rustika (Journal of Ultimate Public Health, 2018)
None